Relaksasi Benson sebagai Terapi Komplementer untuk Nyeri Pascaoperasi - Sulistyo, Angger Hadi; Julianto, Errix Kristian; Naim, Ernin Alfian (Journal of Bionursing, 2024)
Background: Postoperative pain is a condition where a person feels subjective feelings of discomfort after operation. This study aims to analyze the effect of Benson Relaxation on changes in pain in post-operative patients in Surgical Room I, RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro. This research was conducted in August 2022. Methods: The design of this research was pre-experimental with a pre-post test design. The population is all post-op patients in Surgical Room I, RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro in April 2023 as many as 536 patients, with a total sample of 53 people. The sampling technique uses purposive sampling. Data was collected by distributing questionnaires to post-operative pain patients. Results: Based on the results of this study, it was found that almost all 44 respondents (83.0%) experienced moderate pain before being given Benson Relaxation. After being given Benson Relaxation, almost all respondents experienced mild pain, 41 (77.4%). The Wilcoxon test results obtained a Z-Score value of -5.333 and a significant p value of 0.000, meaning that the p value in this study was smaller than a (0.05) or below 0.05 so that H1 was accepted. Conclusion: The conclusion is that there is an effect of Benson relaxation on reducing pain in post-operative patients, because there is a release of endorphins in the brain, so this therapy can be applied in Surgery Room I at Dr. RSUD. R. Sosodoro Djatikoesoemo Bojonegoro.